Catalytic Asymmetric Transannulation of NH‐1, 2, 3‐Triazoles with Olefins1. Issue 13 (14th February 2014) - Kwok, Sen Wai; Zhang, Li; Grimster, Neil P.; Fokin, Valery V.
Abstract A convenient one‐pot asymmetric synthesis of 2, 3‐dihydropyrroles from in situ generated triflated triazoles and olefins is described that further expands the utility of azavinyl carbene chemistry and provides access to an important class of cyclic enamides. Mechanistic investigations support the involvement of triflated cyclopropylaldimine intermediates in the formation of 2, 3‐dihydropyrrole. To the best of our knowledge, this is the first example of a chiral Brønsted acid catalyzed rearrangement of cyclopropylimines into enantioenriched 2, 3‐dihydropyrroles.